PENGARUH PEMBIAYAAN MURABAHAH, MUSYARAKAH, DAN QARDH TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Zelfia Khairani; Hesi Eka Puteri (CV. Adiba Aisha Amira, 2024)
The development of world sharia banking is growing and developing rapidly, including Indonesia. The growth of sharia banking in Indonesia can be seen from the success of banks as intermediary institutions that carry out activities to collect funds from parties (surpus unit) to parties who need funds (deficit unit). Channeling these funds is called financing. The focus of this research is to look at the distribution of financing to Sharia Banks. The aim of this research is to see the impact of BTPN Syariah Bank financing distribution on the profitability (ROA) of sharia banks. The financing carried out by BTPN Syariah is Murabaha financing, Musyarakah financing and Qard financing. This research uses secondary data, namely the published reports of Bank BTPN Syariah for the 2019-2022 period. The analytical tool used in this research is SPSS 25 with multiple linear regression analysis. The results of this research show that Murabahah financing has an impact on the profitability of Islamic banks. Meanwhile, Muayarakah and Qard financing have no effect on the profitability of Islamic banks.